THE EFFECT OF TWO STAY-TWO STRAY STRATEGY ON READING COMPREHENSION OF THE SECOND YEAR STUDENT OF SMPN 34 PEKANBARU - Febrian, Nurma; Aruan, Rumiri; Delfi, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was aimed at investigating the effect of Two Stay-Two Stay strategy on reading comprehension of the second year students of SMPN 34 Pekanbar. This study was an experimental quantitative research. The population of this research was all the second year students of SMPN 34 Pekanbaru. This research was conducted by applying Two Stay-Two Stay (TS-TS) strategy to the experimental group selected by employing cluster random sampling method. There were 40 students in experimental group who had a pre-test and there were 40 students in control group who had a pre-test. Then they were taught by using TS-TS for experimental group, and without TS-TS for control group. They finally had a post-test to see the increase of their scores. After all data were collected, the researcher calculated them by using t-Test method in Ms. Excel 2010. The result of data analysis showed that the mean score of pre-test for control class was 58,12 and the post –test was 62,25. While the result of pre-test for experimental group was 62,62 and the post test was 71,38. With the t-Test score was 8,76, it can be concluded that there was a significant effect of using Two Stay-Two Stray strategy on reading comprehension of the second year students of SMPN 34 Pekanbaru that it could be seen from the improvement of students’ scores in post-test. Therefore, the use of TSTS in teaching reading comprehension is an effective way to improve the students‟ ability. It further increased their self-confidence, social interaction, individual accountability and group skills as well as getting better reading comprehension because they could understand the materials better by learning together as a team.Key Words: Cooperative Learning, Two Stay Two Stray, Reading Comprehension